Pleistocene Archaeology Migration, Technology, and Adaptation - Ono, Rintaro; Pawlik, Alfred (IntechOpen, 2020)
This book presents an overview of recent research in the field of Pleistocene Archaeology around the world. The main topics of this book are: (1) human migrations, particularly by Homo sapiens who have migrated into most regions of the world and settled in different environments, (2) the development of human technology from early to archaic hominins and Homo sapiens, and (3) human adaptation to new environments and responses to environmental changes caused by climate changes during the Pleistocene. With such perspectives in mind, this book contains a total of nine insightful and stimulating chapters on these topics, in which human history during the time of the Pleistocene is reviewed and discussed.